A Matter of Life and Death: Situating Death in Education - Kathy Kortes-Miller (Canadian Society for Studies in Education, 2014)
Abstract Death holds a significant place in our social and cultural worlds despite it not being a direct or first-hand experience for many of us. Informal education about death occurs regularly throughout our daily lives in the context of "teachable moments, the unplanned life events from which important lessons can be drawn" (Kastenbaum, 2007, p. 483). Building upon a meaningful clinical encounter with a woman who was dying, this literature review explores the need to situate death as a topic and as a curriculum within the broad context of education and across the lifespan. By exploring some of the relevant discourses on death relating to education, I identify ways in which we receive death education informally through media, religion, culture, and the arts, presenting an argument for more formalized death education within all systems and levels of education.